Ultrathin flat microwave transmitarray antenna for dual‐polarised operations. Issue 20 (1st September 2016) - Chen, Lv‐Wei; Ge, Yuehe; Bird, Trevor S.
Abstract : A dual‐polarised phase‐correcting microwave transmitarray that is based on an ultrathin phase‐shifting surface (PSS) has been developed at 22 GHz. The FSS element in this array has a square shape with the rotationally symmetrical geometry. It consists of two identical metallic layers etched on the two sides of a single dielectric layer. A phase‐shifting range of about 330° is achieved. A planar slot‐fed patch antenna was developed as the feed source for the compact structure. The transmitarray prototype, which is fed by a planar antenna, as well as a standard horn, was measured separately. The results show that peak gains of 25.82 and 27.45 dBi and 1 dB gain bandwidths of 6.8 and 9.5% are achieved for the two feed cases.